Implications of Supreme Court Jurisprudence No.1400k/Pdt/1986 on Marriage Different Religions - Nofrizal Nofrizal; Zulkifli Zulkifli; Hayatul Ismi; Ulfia Hasanah; Putri Annisa (Unram Law Review, 2022)
In Indonesian law, Marriage Law does not provide for marriages of different religions. Thus, Indonesia's positive law does not recognize the term interfaith or interfaith marriage. But, after the Supreme Court decision Number 1400K / Pdt / 1986, the existence of interfaith marriage in Indonesia is getting bigger. Supreme Court Decision No. 1400k/Pdt/1986, states that couples of different faiths can ask for a court determination. However, Constitutional Court Decision No.68/PUU-XII/2014 rejected the legalization of interfaith marriage. This research is normative legal research, as it is based on library research that takes reference from text books, as well as supporting data related to the problem studied assisted by primary, secondary and tertiary data sources. This research uses qualitative data analysis and produces descriptive data. From the results of the study, it was concluded that, first, the position of interfaith marriage in Indonesia is not regulated in Law No. 1 of 1974 concerning Marriage and the latest Marriage Law, namely Law No. 16 of 2019 concerning Marriage. The regulation of interfaith marriage in Indonesia at this time is based on the jurisprudence of Supreme Court Decision No. 1400K / Pdt / 1986. Second, the position of interfaith marriage in Indonesia according to the Constitutional Court Decree No. 86/PUU-XII/2014 is prohibited because interfaith marriage is not by the values of the Godhead in the First Precept of Pancasila, it is also contrary to the 1945 Constitution and contrary to the values of Pancasila.. However, in some plea for interfaith marriage in the court by the bride and the groom, the judge did not abide to constitutional court decision No. 86/PUU-XII/2014, so the implementation of the constitutional court's decision was ineffective. Meanwhile, in principle, according to the jurisprudence of Supreme Court Decision No. 1400K/Pdt/1986, the State merely responsible for the registration of interfaith marriages, and is not responsible for the legitimacy of interfaith marriages.